2009
DOI: 10.1002/ccd.22194
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of drug‐eluting stents versus bare‐metal stents in saphenous vein graft disease: Results from the Prairie “Real World” Stent Registry

Abstract: Objectives: This study was designed to compare long-term clinical outcomes of drugeluting stents (DES) versus bare metal stents (BMS) in patients with saphenous vein graft (SVG) disease in the ''real world.'' Background: The safety and efficacy of DES versus BMS in SVG remains uncertain due to contradictory reports of either lower revascularization rates with DES; or clinical equivalence to BMS; or even an excess of clinical events associated with DES use. Methods: We identified consecutive patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 31 publications
(36 reference statements)
0
13
0
1
Order By: Relevance
“…Periprocedural treatment with clopidogrel was more disparate among eligible studies. In most trials, clopidogrel was prescribed for at least 1 month after BMS placement 13,[17][18][19][21][22][23]25,[27][28][29]36 and for at least 3 18 -20,22,25,28 or 6 months 13,14,17,19,21,23,25,27,28,32,33,36,37 after DES implantation. In the DELAYED RISCC study, 12 clopidogrel was administered for at least 2 months in all patients.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Periprocedural treatment with clopidogrel was more disparate among eligible studies. In most trials, clopidogrel was prescribed for at least 1 month after BMS placement 13,[17][18][19][21][22][23]25,[27][28][29]36 and for at least 3 18 -20,22,25,28 or 6 months 13,14,17,19,21,23,25,27,28,32,33,36,37 after DES implantation. In the DELAYED RISCC study, 12 clopidogrel was administered for at least 2 months in all patients.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Stent thrombosis rates were available in only 15 studies. [12][13][14][15][17][18][19]21,22,24,25,27,30,33,36 Although the OR point estimate (OR, 0.54) suggests reduced risk for stent thrombosis with DES, the wide 95% CrI (0.13 to 1.39) precludes definitive conclusions regarding any benefit of DES over BMS (Figure 7) with regard to this specific end point.…”
Section: Meta-analysis Of Studied Outcomes Measuresmentioning
confidence: 99%
“…7 Depois desses estudos randomizados iniciais realizados em pequenos grupos, foram apresentadas muitas séries de populações do mundo real com lesões em EVS. [11][12][13][14][15][16][17][18][19][20] Recentemente foram publicadas duas metaanálises de ensaios randomizados e estudos observacionais, abrangendo mais de 5 mil pacientes. Meir et al 21 relataram taxas semelhantes de morte, IM e RLA em pacientes tratados com stents farmacológicos e stents não-farmacológicos em ensaios randomizados.…”
Section: Discussionunclassified
“…In their meta-analysis, DESs were found to be superior to BMSs with regard to the incidence rates of MACEs (19 vs. 28%, P<0.00001), mortality (31). By contrast, other studies did not find DESs to be superior to BMSs in the long-term follow-up subsequent to SVG-PCI (17,32,33). The SOS study (17) found that the overall mortality rate did not differ significantly between the DES and BMS groups at the end of 1.5 years of follow-up (5 vs. 12%; HR, 1.56; 95% CI, 0.72-4.11; P=0.27).…”
Section: A B C Dmentioning
confidence: 95%
“…In a study of 284 patients with DESs and 95 patients with BMSs, the incidence of MACEs at 3 years did not differ significantly between the groups, despite a significantly higher inpatient mortality rate in the BMS group. This suggested a good safety profile (but non-superiority) of DESs in long-term implantation (33).…”
Section: A B C Dmentioning
confidence: 98%